2020
DOI: 10.30544/537
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the position of parallelogram ribs in micro channel on heat transfer using diamond nanoparticles

Abstract: In the present work, we have studied numerically three dimensions, the impact of the position of parallelogram ribs in a micro-channel on thermal exchange. In this study, we proposed three cases of micro-channel heat sinks with parallelogram ribs. As well as one case without ribs, in each of the three cases, we varied the parallelogram rib positions on the micro-channel. The main purpose of this study is to find the best position for parallelograms ribs in which the heat dissipation is useful for improving the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Farsad et al [13] found that the small vorticities currents generated by the dimples play a role in enhancing turbulent mixing and heat transfer, and this effect increases significantly with the increase of Reynolds number. Moreover, several studies have been performed on the influence of Reynolds number on the friction factor [15] and Nusselt number [16][17][18][19][20][21][22][23][24]. For example, Chadi et al [15] found that, as the Reynolds number increases, the Nusselt number and the friction factor increase and decrease, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Farsad et al [13] found that the small vorticities currents generated by the dimples play a role in enhancing turbulent mixing and heat transfer, and this effect increases significantly with the increase of Reynolds number. Moreover, several studies have been performed on the influence of Reynolds number on the friction factor [15] and Nusselt number [16][17][18][19][20][21][22][23][24]. For example, Chadi et al [15] found that, as the Reynolds number increases, the Nusselt number and the friction factor increase and decrease, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies have been performed on the influence of Reynolds number on the friction factor [15] and Nusselt number [16][17][18][19][20][21][22][23][24]. For example, Chadi et al [15] found that, as the Reynolds number increases, the Nusselt number and the friction factor increase and decrease, respectively. Compared with traditional heat sinks, Vajravel et al [19] showed that the above rules are more obvious in microchannel heat sinks; that is, with the increase of the Reynolds number, the Nusselt number increases faster.…”
Section: Introductionmentioning
confidence: 99%